Desempenho da gestão de processos das construtoras de Pau dos Ferros/RN - Lira, Felipe Medeiros (Universidade Federal Rural do Semi-Árido, 2018)
Process management improves the efficiency of the building process to maximize the company's resources. This work aims to perform a diagnosis of the performance in the processors' construction management in the municipality of Pau dos Ferros/RN by describing the activities processes and services performed by these enterprises. The methodology of process management, which has three phases, process definition, process analysis and process improvement serves as a theoretical basis in the development of this work. The methodological procedures of this research were: bibliographical research and data collection in the field through questionnaires. It was verified in the 11 works investigated that 90,91% are in urban perimeter and 9,09% in rural areas, 100% of the works had schedules, 27,27% with final deadlines of the works around 12 months, but 100% with some adjustments in their initial projects to meet deadlines. It was also verified that the main impacts in the works are related to the neglect in the performance analysis. It was evidenced that the proposition of process management guidelines has improvements on the general aspects of construction. Therefore, it is necessary to invest in actions that contribute to the improvement of this management activity, to assure the legality of this commercial arrangement.
Keywords: Construções; Gestão de processos; Índice de desempenho; ENGENHARIAS::ENGENHARIA CIVIL